2010
DOI: 10.1038/aja.2009.98
|View full text |Cite
|
Sign up to set email alerts
|

Molecular heterogeneity of gelatin-binding proteins from human seminal plasma

Abstract: Defining the molecular characteristics of seminal plasma proteins is essential for understanding their function in physiological and pathological conditions. Starting from the predicted importance of human seminal plasma gelatin-binding proteins, comprising fibronectin (FN) and FN-related molecules, for male fertility, this study aims at gaining insight into their immuno-glycobiochemical properties. Human seminal plasma from subjects with normal semen parameters were separated on a gelatin-Sepharose column and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…Group of HBPs (14)(15)(16)(17)(18) are the same as BSP proteins (Therien et al, 1995). 1 Cattle BSP-A1/-A2 (PDC-109), BSP-A3, BSP-30-kDa Esch et al (1983) 2 Rat, Hamster BSP-like antigens Leblond et al (1993) 3 Stallion HSP-1, -2, -12-kDa Calvete et al (1995a) 4 Swine pB-1 Calvete et al (1997) 5 Goat GSP-14, -15, -20, -22-kDa Villemoure et al (2003) 6 Sheep BSP-like antigen Bergeron et al (2005) 7 Buffalo BSP-like antigen Arangasamy et al (2005) 8 Human BSP-like antigen Kosanović and Jankovi (2010) …”
Section: Bovine Seminal Plasma Proteinsmentioning
confidence: 97%
“…Group of HBPs (14)(15)(16)(17)(18) are the same as BSP proteins (Therien et al, 1995). 1 Cattle BSP-A1/-A2 (PDC-109), BSP-A3, BSP-30-kDa Esch et al (1983) 2 Rat, Hamster BSP-like antigens Leblond et al (1993) 3 Stallion HSP-1, -2, -12-kDa Calvete et al (1995a) 4 Swine pB-1 Calvete et al (1997) 5 Goat GSP-14, -15, -20, -22-kDa Villemoure et al (2003) 6 Sheep BSP-like antigen Bergeron et al (2005) 7 Buffalo BSP-like antigen Arangasamy et al (2005) 8 Human BSP-like antigen Kosanović and Jankovi (2010) …”
Section: Bovine Seminal Plasma Proteinsmentioning
confidence: 97%
“…Sperm is considered as a highly diverse antigenic cell, it contains antigens that can be modified during processes of maturation and ejaculation, e.g. the binding of soluble fibronectin to the tail of sperm [2]. During the early years of the 20th century, researchers had shown that spermatozoal and seminal plasma antigenic components can stimulate both specific autoimmunity and isoimmunity.…”
Section: Introductionmentioning
confidence: 99%
“…The reactivities of normal seminal plasma fibronectin with fucose-specific AAL and UEA, and sialo-specific MAA and SNA suggest that FN is heavily fucosylated through the α1,6and α1,2-types of linkages, but weakly by α1,3-linked fucose, and is poorly sialylated ( Table 1). The presence of fucose α1,6-linked in seminal fibronectin has been proved by Kosanović and Janković [17]. Human blood plasma α 1 -acid glycoprotein does not contain α1,6and α1,2linked fucoses, but contains variable amount of fucose α1,3-linked, and is heavily sialylated, mainly through α2,6-type of linkage [18,34,37].…”
Section: Discussionmentioning
confidence: 91%
“…Seminal plasma totally lacks the intact fibronectin form and consists of FN fragments derived from those FN domains which are known to be glycosylated, i.e. the cell-binding domain [15,35] and collagendomain [17]. Distribution of hypo-and a-sialylated FN glycoforms has been found to be associated with abnormal semen parameters and with high concentrations of fibronectin [14].…”
Section: Introductionmentioning
confidence: 99%